Urgensi Penerapan Konsep Green Banking di Indonesia - Barran Hamzah Nasution; Rosa Agustina; Affila (DOKTRINA: JOURNAL OF LAW, 2023)
Era globalization, environmental management and protection become important matters. Environmental issues nowadays have become not only local or trans-local issues but also regional, national, transnational, and global issues. On that matter, banks in Indonesia transform their business activities by implementing the green banking concept, in which national banks nowadays consider environmental management and protection aspects in their operational activities. However, the absence of statutory regulations in Indonesia which explicitly stipulate obligations for a bank to include provisions for environmental management and protection requires legal renewal in the application of the green banking concept to banking management in Indonesia. This research aims to review the definition and history of green banking and the urgency of the green banking concept implementation in Indonesia. This research is normative legal research in which using a statute approach. The legal materials used in this research are derived from primary and secondary legal materials. The legal material collection technique used in this research is a library research technique. The data in which sourced from legal materials in this study were analyzed using a qualitative approach.